2001
DOI: 10.1067/mtc.2001.112343
|View full text |Cite
|
Sign up to set email alerts
|

Methylprednisolone does not benefit patients undergoing coronary artery bypass grafting and early tracheal extubation

Abstract: Methylprednisolone, as used in this investigation, offers no clinical benefits to patients undergoing elective coronary artery bypass grafting with cardiopulmonary bypass and may in fact be detrimental by initiating postoperative hyperglycemia and possibly hindering early postoperative tracheal extubation for undetermined reasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 32 publications
0
42
1
Order By: Relevance
“…Moreover, two recent clinical investigations of steroid administration in adults demonstrated no benefit or even an adverse outcome after steroid administration [4,9,24]. However, in children, Schroeder et al [23] demonstrated improved oxygen delivery in the first 24 hours after congenital heart surgery with combined pre-and intraoperative steroid administration, but no significant difference was shown between the length of mechanical ventilation and the inotropic support.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two recent clinical investigations of steroid administration in adults demonstrated no benefit or even an adverse outcome after steroid administration [4,9,24]. However, in children, Schroeder et al [23] demonstrated improved oxygen delivery in the first 24 hours after congenital heart surgery with combined pre-and intraoperative steroid administration, but no significant difference was shown between the length of mechanical ventilation and the inotropic support.…”
Section: Discussionmentioning
confidence: 99%
“…In patients who are undergoing cardiac surgery, acute administration of methylprednisolone reduces postoperative interleukin-6 secretion but offers no clinical benefits. [18][19][20] However, in the peripheral vasculature, normalization of elevated hsCRP concentrations over time is associated with a normalization of endothelium-mediated flow after 3 months in patients with coronary artery disease. 45 Thus, in the present study dxinduced anti-inflammatory period for 2 days might be too short to improve coronary vascular resistance in obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, reduced coronary vasoreactivity can be improved by medical interventions. 16,17 Clucocorticoids suppress secretion of inflammatory cytokines [18][19][20] and some animal studies have demonstrated beneficial effects of glucocorticoids during myocardial ischemia. 21,22 Still, clucocorticoids appear not to benefit patients undergoing coronary artery bypass grafting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…System inflammatory response syndrome (SIRS) is the main cause of pulmonary dysfunction after CPB [2]. Although many strategies to attenuate SIRS have been developed [3], it has not been completely prevented and remains a significant contributor to pulmonary dysfunction after surgery [2,4,5].SIRS is mainly caused by the contact of blood with the non-endothelialised surface of CPB circuits activating multiple plasma protein cascades and blood cells, resulting in increased production of inflammatory mediators and activation of vascular endothelium [3,4]. Activated polymorphonucleocytes (PMNs) sequestered in the lung in response to chemotactic factor interleukin-8 (IL-8) may result in widespread pulmonary inflammatory response and injury through the release of harmful oxygen free radicals and specific enzymes [6,7].…”
mentioning
confidence: 99%